Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1074/jbc.m114.573592
|View full text |Cite
|
Sign up to set email alerts
|

miR-15b/16-2 Regulates Factors That Promote p53 Phosphorylation and Augments the DNA Damage Response following Radiation in the Lung

Abstract: Background:MicroRNAs play an integral role in modulating cellular stress, including DNA damage. Results: miR-15b induces p53 phosphorylation, DNA repair, apoptosis, and cell cycle arrest while inhibiting Wip1 expression following irradiation in lung epithelial cells. Conclusion:The miR-15b/Wip1 axis could be a potential therapeutic target in radiation-associated lung disease. Significance: MicroRNAs may represent an actionable target in the lung following radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 33 publications
0
26
0
2
Order By: Relevance
“…24 In addition, miR15b has been established to be up-regulated following exposure to diverse stress-inducing agents, including ionizing radiation, etoposide, and hydrogen peroxide, which significantly influenced the cell cycle progression by targeting WIP1. 25 The demonstration that miR-33b-3p was dramatically downregulated when exposed to cisplatin and impacted on DDR by negative regulation of p21, further enlarged the knowledge and confirmed the effects of miRNAs on DNA damage response.…”
Section: Discussionmentioning
confidence: 80%
“…24 In addition, miR15b has been established to be up-regulated following exposure to diverse stress-inducing agents, including ionizing radiation, etoposide, and hydrogen peroxide, which significantly influenced the cell cycle progression by targeting WIP1. 25 The demonstration that miR-33b-3p was dramatically downregulated when exposed to cisplatin and impacted on DDR by negative regulation of p21, further enlarged the knowledge and confirmed the effects of miRNAs on DNA damage response.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, many of the controls in other studies did not undergo radiological investigations, such as computed tomography, whereas all the cases did in the present study. It is, therefore, possible that some of the changes in miRNA expression noted here are actually consequent to radiation exposure 33 . Finally, the recent discovery that miRNAs are present in the circulation has sparked interest in their use as potential biomarkers.…”
Section: Figurementioning
confidence: 97%
“…miR-194-5p and miR-30a-5p have been shown to be associated with epithelial-mesenchymal transition, which is one of the hallmarks of more aggressive cancers [21,22]. Recent studies have demonstrated an important role for miR-15b-5p (and miR-16-5p that lies in the same genomic cluster), in regulating apoptosis, cell cycle and DNA repair pathways [23], and highlighted miR-15b-5p as a potential target for anti-cancer therapies [24]. Finally, miR-17-5p belongs to one of the most well-studied oncogenic miRNA clusters, miR-17/92, commonly found to be overexpressed in solid tumors including gastric and colorectal cancers [25].…”
Section: Discussionmentioning
confidence: 99%